Genetics of Male Infertility - Nilam Thakur; Ajit Saxena; Amar Prakash Garg (Janaki Medical College Journal of Medical Science, 2025)
Infertility is defined as the inability to conceive after at least one year of regular, unprotected sex. This affects 15–20% of couples and estimated to affect 72.4 million people globally. According to WHO, 9% of couples worldwide struggle with fertility issues and the male factor accounts for 50% of couple sub-fertility with only responsibility in 30% of cases and a co-contributing female factor in 20% of factors. Male infertility is widely known to be partially caused by genetic disorders. Genetic abnormalities can affect spermatogenesis, hormone regulation, and reproductive tract development, leading to various forms of male infertility. This review paper provides an in-depth analysis of the genetic factors contributing to male infertility, including chromosomal abnormalities, single-gene mutations, and Y chromosome microdeletions.